2017
DOI: 10.1007/s00284-017-1272-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Composition of Gut Bifidobacterium Species

Abstract: Bifidobacteria are one of the major components in human microbiota that are suggested to function in maintaining human health. The colonization and cell number of Bifidobacterium species in human intestine vary with ageing. However, sequential changes of Bifidobacterium species ranging from newborns to centenarians remain unresolved. Here, we investigated the gut compositional changes of Bifidobacterium species over a wide range of ages. Faecal samples of 441 healthy Japanese subjects between the ages of 0 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
104
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 46 publications
12
104
1
Order By: Relevance
“…Bifidobacterium is the well-known probiotic dominating in human gut microbiota and reduces with age [35]. Similar to the observation that Bifidobacterium disappears in middle-aged mice,[12] our data reveal that Bifidobacterium is the genus declined mostly in human midlife.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Bifidobacterium is the well-known probiotic dominating in human gut microbiota and reduces with age [35]. Similar to the observation that Bifidobacterium disappears in middle-aged mice,[12] our data reveal that Bifidobacterium is the genus declined mostly in human midlife.…”
supporting
confidence: 89%
“…This is supported by a recent study that changes in the composition of Bifidobacterium species occur with ageing. [35] Addition to the roles of acetate in the healthy problem of midlife, such as obesity and T2D, it is reported that bifidobacteria-produced acetate improves intestinal defense mediated by epithelial cells and thereby protects the host against lethal infections. [62] Therefore, further study is needed to clarify the species of Bifidobacterium reduced in midlife.…”
Section: Discussionmentioning
confidence: 99%
“…1e ). In contrast, post weaning type Bifidobacterium species, including B. adolescentis , B. animalis/pseudolongum and B. catenulatum group 20, 21 , were not significantly associated with aromatic lactic acids nor breastfeeding status ( Fig. 1e ).…”
Section: Resultsmentioning
confidence: 93%
“…Bifidobacterium animalis subsp. lactis is considered to be a subspecies of nonendogenous bifidobacteria in the human gut (Kato et al, ; Turroni et al, ). In this study, the number of B. lactis was above the detection limit in the feces of only five subjects during the observation period and their levels were very low.…”
Section: Discussionmentioning
confidence: 99%